ChemInform Abstract: The Synthesis and Structure of Chiral Enamine N‐Oxides. Issue 48 (2nd December 2014) - O'Neil, I. A.; McConville, M.; Zhou, K.; Brooke, C.; Robertson, C. M.; Berry, N. G.
Abstract The reaction does not tolerate alkyl, aryl, or silyl substituents on monoactivated alkynes.